Pemahaman Fenomena Work Values dan Big Five Personality Traits dalam Retensi dan Perilaku Menyimpang Karyawan Generasi Z - Nayla Rahma Aulia; Renny Husniati; Nasywa Khoerun Nadhifa; Luvena Keisya Audrey Febriana; Vanesa Cathy Gultom; Nauragita Risqy Alifa (MANAJEMEN, 2026)
The demographic transition in the workforce identifies Generation Z as a crucial cohort with unique work values, prioritizing work-life balance and meaningful work over financial compensation. This study aims to evaluate the influence of work values and the Big Five Personality Traits on retention and deviant workplace behavior among Generation Z employees. Utilizing a qualitative library research method with content analysis, this research synthesizes current academic literature. The findings indicate that misalignment between individual work values and organizational systems triggers high turnover intention. Specifically, the personality dimensions of conscientiousness and agreeableness are proven to strengthen retention, while neuroticism correlates positively with stress and deviant behavior. As a managerial implication, organizations are advised to adopt adaptive HR strategies that support mental health to retain young talent. This study is limited by its reliance on secondary data; therefore, future empirical research is necessary to validate these findings.